Label-free, fast, 2-photon volume imaging of the organization of neurons and glia in the enteric nervous system - Hazart, Doriane; Delhomme, Brigitte; Oheim, Martin; Ricard, Clément (Frontiers in Neuroanatomy, 2023)
The enteric nervous system (ENS), sometimes referred to as a “second brain” is a quasi-autonomous nervous system, made up of interconnected plexuses organized in a mesh-like network lining the gastrointestinal tract. Originally described as an actor in the regulation of digestion, bowel contraction, and intestinal secretion, the implications of the ENS in various central neuropathologies has recently been demonstrated. However, with a few exceptions, the morphology and pathologic alterations of the ENS have mostly been studied on thin sections of the intestinal wall or, alternatively, in dissected explants. Precious information on the three-dimensional (3-D) architecture and connectivity is hence lost. Here, we propose the fast, label-free 3-D imaging of the ENS, based on intrinsic signals. We used a custom, fast tissue-clearing protocol based on a high refractive-index aqueous solution to increase the imaging depth and allow us the detection of faint signals and we characterized the autofluorescence (AF) from the various cellular and sub-cellular components of the ENS. Validation by immunofluorescence and spectral recordings complete this groundwork. Then, we demonstrate the rapid acquisition of detailed 3-D image stacks from unlabeled mouse ileum and colon, across the whole intestinal wall and including both the myenteric and submucosal enteric nervous plexuses using a new spinning-disk two-photon (2P) microscope. The combination of fast clearing (less than 15 min for 73% transparency), AF detection and rapid volume imaging [less than 1 min for the acquisition of a z-stack of 100 planes (150*150 μm) at sub-300-nm spatial resolution] opens up the possibility for new applications in fundamental and clinical research.